Neurochondrin Autoimmunity With Slow Saccades: A Case Report. (5th December 2022) - Tanke, Laurel; Eggenberger, Eric; Pless, Misha
Abstract : Objective: N/A. Background: Neurochondrin is a cytoplasmic neuronal antigen that can be targeted by specific antibodies, resulting in an antigen-specific T-cell response and autoimmune cerebellar and brain stem degeneration.1 Previously reported cases of neurochondrin antibody positivity have been predominantly associated with rapidly-progressive rhombencephalitis, but various other neurological symptoms and signs may be present.1, 2 Design/Methods: N/A. Results: 34-year-old woman presented with 2 years of constant numbness in her toes, gradually worsening to involve the entire lower and upper extremities. She also reported dysarthria, imbalance, and leg spasticity. Neurological examination showed a slow, wide-based gait, brisk reflexes bilaterally, and bilateral extensor plantar responses. MRI brain was normal and CSF analysis showed 7 oligoclonal bands. The patient was diagnosed with probable multiple sclerosis and steroids were initiated but resulted in no improvement of symptoms. Plasmapheresis was also ineffective. 3 months later, MRI showed subtly increased T2 signal of the central cord mainly involving the gray matter at the level of C5 and C6. CSF analysis showed 15 oligoclonal bands and an elevated IgG index of 1.39. VDRL was nonreactive. HTLV, ANCA, AQP4, CSF VZ PCR, HSV PCR, and HHV6 PCR were all negative. EMG showed mild length-dependent axonal sensory motor peripheral neuropathy. On neuro-ophthalmic examination, the patient showed slowed saccades with some preservation of optokinetic nystagmus (OKN) fast phases. Repeat MR showed abnormal T2 hyperintensity in the anterior horns of the gray matter from C1-2 to T1. Serum testing at that time showed a positive neurochondrin antibody. She was then started on cyclophosphamide and mycophenolate mofetil. 6 months after initiation of cyclophosphamide, dysarthria and upper limb mobility improved, and she had no further neurological deterioration at that time. Conclusions: Neurochondrin IgG-related autoimmunity is rare and can result in a wide variety of neurological signs and symptoms. Ocular dysmotility, including slowed saccades, may be present.